Nitrogen variability assessment in tomatoes using the remote sensing technique for precision farming - Bodirwa, Kgashane Bethuel (My University, 2009)
The purpose of the study was to assess nitrogen variability in tomato using the Remote Sensing Technique. The assessment was carried out through three growth stages (seedling, 50% flowering, and 50% fruiting stage). The GreenSeeker optical sensor unit that records NDVI values and total leafy nitrogen analyzer, “The Primacssn Nitrogen Analyzer,” was used in this study for data collection. Fertilizers were applied to the soil (Urea - 46% N, Superphosphate) every two weeks in the pots only for the treated experiment, and no nitrogen application for the untreated experiment. Tomato cultivars Flora Dade and Roma VF were used during the experimentation. The mean NDVI values for cultivars Flora Dade and Roma VF were 0.83 with N application. This value was 0.81 without N-application. The mean N-content for cultivars Flora Dade and Roma VF were 3.30 g/plant with N application. This value was 2.94 g/plant without N-application. The cultivar Flora Dade with N applied had higher N-content (3.38 g/plant) than the cultivar Roma VF with 3.22 g/plant when no N is applied across the three growth stages. The number of fruits’ means values at 50% fruiting stage for cultivars Flora Dade and Roma VF were 8.9 fruit per plant with N application. These mean values were 5 fruit per plant without N application. It was also evident that plants likely to have lower N content (untreated) had delayed maturation unlike those with nitrogen applied (treated), which had rapid/early maturation. Untreated plants took an average of 120 days till maturity, whereas the treated plants took an average of 100 days till maturity. Ground measurement of NDVI by the GreenSeeker sensor in this study showed potential for assessing nitrogen variability in tomato.
Thesis (M.Sc. (Agriculture)) --University of Limpopo, 2009
Keywords: Tomatoes; Remote sensing technique; Precision farming; 635.642; Precision farming